Endobronchial ultrasound in diagnosing and staging of lung cancer by Acquire 22G TBNB versus regular 22G TBNA needles: study protocol of a randomised clinical trial - Kuijvenhoven, Jolanda C; Kramer, Tess; Korevaar, Daniël A; Ninaber, Maarten K; Trisolini, Rocco; Szlubowski, Artur; Gnass, Maciej; von der Thüsen, Jan; Cohen, Danielle; Bonta, Peter I; Annema, Jouke T (BMJ open, 2021)
IntroductionAccurate diagnosis and staging of lung cancer is crucial because it directs treatment and prognosis. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) and endoscopic ultrasound with bronchoscope fine-needle aspiration (EUS-B-FNA) are important in this process by sampling hilar/mediastinal lymph nodes and centrally located lung tumours. With the upcoming of immunotherapy and targeted therapies, assessment of programmed death ligand 1 (PD-L1) expression and molecular profiling has become important but is often impossible in cytological samples obtained through standard 22G TBNA needles. Recently, a three-pronged cutting edge 22G needle was developed that allows for transbronchial needle biopsy (TBNB). Our objective is to determine if EBUS/EUS-B-guided nodal/lung tumour sampling with Acquire 22G TBNB needles results in an improved suitability rate for the assessment of PD-L1 expression in comparison to standard 22G TBNA needles in patients with a final diagnosis of lung cancer.Methods and analysisThis is an investigator-initiated, parallel group randomised clinical trial. Patients are recruited at respiratory medicine outpatient clinics of participating university and general hospitals in the Netherlands, Poland and Italy. In total 158 adult patients with (suspected) lung cancer are included if they have an indication for mediastinal/hilar lymph node or lung tumour sampling by EBUS-TBNA and/or EUS-B-FNA based on current clinical guidelines. Web-based randomisation between the two needles will be performed. Samples obtained from mediastinal/hilar lymph nodes and/or primary tumour will be processed for cytology smears and cell block analysis and reviewed by blinded reference pathologists. An intention-to-treat analysis will be applied. Patients with missing data will be excluded from analysis for that specific variable but included in the analysis of other variables. This study is financially supported by Boston Scientific.Ethics and disseminationThe study was approved by the local Ethics Committee (Medisch Ethische Toetsingscommissie Amsterdam Medical Center (AMC)). Dissemination will involve publication in a peer-reviewed biomedical journal.Trial registration numberNL7701; Pre-results.